2022
DOI: 10.1021/acs.analchem.1c04373
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Parameter Dependencies in High-Field Asymmetric Waveform Ion-Mobility Spectrometry and Size Exclusion Chromatography for Proteome-wide Cross-Linking Mass Spectrometry

Abstract: Ion-mobility spectrometry shows great promise to tackle analytically challenging research questions by adding another separation dimension to liquid chromatography–mass spectrometry. The understanding of how analyte properties influence ion mobility has increased through recent studies, but no clear rationale for the design of customized experimental settings has emerged. Here, we leverage machine learning to deepen our understanding of field asymmetric waveform ion-mobility spectrometry for the analysis of cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…In addition, PP3, peptide predicted charge when pH = 7, the Cruciani property H-bonding descriptor, and other QSAR features also contributed to the model. It is also worth noting that a recent study by Sinn et al examined the factors contributing to the FAIMS-based separation of cross-linked peptides and identified a similar collection of determinants.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, PP3, peptide predicted charge when pH = 7, the Cruciani property H-bonding descriptor, and other QSAR features also contributed to the model. It is also worth noting that a recent study by Sinn et al examined the factors contributing to the FAIMS-based separation of cross-linked peptides and identified a similar collection of determinants.…”
Section: Resultsmentioning
confidence: 96%
“…Previous reports have shown that a peptide isoform’s ability to pass through the FAIMS device at a given CV value can be weakly correlated with the charge state. However, the identification of other physicochemical properties displaying a clear correlation with FAIMS transmission is only now emerging. ,,, Using a machine learning approach, we attempted to identify additional determinants that govern peptide transmission by FAIMS. We built a linear regression model to identify factors that impact peptide detectability and then used Lasso regression to minimize the number of factors in the model.…”
Section: Resultsmentioning
confidence: 99%
“…Because DMS uses a high-voltage dynamic electric field, the measurement of CCS is always a challenge. The calibration method based on machine learning can predict the CCS of compounds. , Ieritano et al used a machine learning-based calibration method to predict the CCS of compounds with an error of 2.6 ± 0.4%, which was very close to the inherent error of 2.2% in CCS calculation . This achievement allows DMS to realize the function of structure characterization rather than just as a filtering technology.…”
Section: Ims and Its Combination Technology Developmentmentioning
confidence: 90%
“…Finally, cross-linked peptides can be enriched in the gas phase after injection into the mass spectrometer. There have been studies showing that the physicochemical properties of cross-linked peptides allow for them to be separated from other species using the FAIMS device [ 57 , 58 ] or ion mobility cells [ 59 ] ( Figure 2 ). This removes highly abundant species that prevent cross-links from being selected for fragmentation and also reduces co-isolation events where two overlapping precursor ions are fragmented producing a messy MS2 spectrum.…”
Section: Strategies For Enriching Cross-links From Complex Samplesmentioning
confidence: 99%